Hypothermic perfusion of donor heart with a preservation solution supplemented by mesenchymal stem cells - Korkmaz-İçöz, Sevil; Li, Shiliang; Ruppert, Mihály; Loganathan, Sivakkanan; Sayour, Alex Ali; Brlecic, Paige; Lasitschka, Felix; Karck, Matthias; Szabó, Gábor; Hüttner, Regina (The journal of heart and lung transplantation, 2019)
BACKGROUND - Heart transplantation is the definitive treatment for end-stage heart failure. A shortage of donor hearts forced transplant programs to accept older donors and longer ischemic times. Previous studies have suggested that administration of mesenchymal stem cells (MSCs) or their conditioned medium (CM) protects the heart against ischemia/reperfusion injury (IRI). We hypothesized that the preservation of donor hearts with a CM would protect the graft from IRI after prolonged storage in 15-month-old rats and investigated mRNA changes attributable to CM. - METHODS - Rat MSCs were isolated and cultured. The CM was used and characterized by a 90-antibody array, revealing the presence of 28 factors involved in apoptosis, inflammation, and oxidative stress. Hearts from 15-month-old donor rats were explanted and continuously perfused for 5 hours with oxygenated, 4°C cardioplegic solution, and supplemented with either regular cell culture medium (control group) or CM. The hearts were then heterotopically transplanted. We evaluated in-vivo left ventricular graft function 1.5 hours after transplantation and the myocardial expression of 120 genes using polymerase chain reaction arrays. - RESULTS - Systolic contractility and relaxation parameters were significantly reduced in 15-month-old rats compared with the young rats. After transplantation, systolic function (dP/dtmax: 1,197 ± 94 vs 1,825 ± 279 mm Hg/s at 140 µl; p < 0.05) and diastolic function (dP/dtmin: 737 ± 168 vs 1,200 ± 166 mm Hg/s at 140 µl, p < 0.05) were significantly improved in the CM group compared with controls. Among the genes surveyed, the expressions of 66 were altered. Genes of pro-inflammatory cytokines and interleukins were down-regulated, whereas expression of the anti-oxidant gene superoxide dismutase-2 was up-regulated in the CM-treated grafts compared with the control group grafts. - CONCLUSIONS - Perfusion of donor hearts with CM protects against myocardial IRI in 15-month-old rats.
Available online 6 December 2018
Gesehen am 06.09.2019